2022
DOI: 10.3390/healthcare10102081
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Antidepressants Utilization for Patients Visiting Psychiatric Out-Patient Clinic in a Tertiary Care Hospital

Abstract: Depression is a prevalent mental health condition treated with antidepressants and other psychotropic medications. This study aimed to assess the utilization pattern of antidepressants among patients visiting the outpatient clinic of the psychiatry department of a tertiary care hospital. The study included the patients who visited the study site and fulfilled the mental and behavioral diagnostic criteria for depression. The demographic and clinical details, including drugs prescribed, were documented in a stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Pharmacological intervention is commonly used to manage clinical depression. A recently conducted drug utilization study in depression patients revealed that escitalopram was the most commonly prescribed antidepressant as monotherapy or in combination [ 3 ]. The study also discovered that polypharmacy involving the simultaneous use of two antidepressants was practiced just as much as any agent alone [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological intervention is commonly used to manage clinical depression. A recently conducted drug utilization study in depression patients revealed that escitalopram was the most commonly prescribed antidepressant as monotherapy or in combination [ 3 ]. The study also discovered that polypharmacy involving the simultaneous use of two antidepressants was practiced just as much as any agent alone [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recently conducted drug utilization study in depression patients revealed that escitalopram was the most commonly prescribed antidepressant as monotherapy or in combination [ 3 ]. The study also discovered that polypharmacy involving the simultaneous use of two antidepressants was practiced just as much as any agent alone [ 3 ]. However, in response to the diminished symptoms or adverse effects associated with these synthetic antidepressants, including withdrawal effects, sexual problems, weight gain, adverse emotional effects, or other factors such as treatment cost, patients tend to discontinue the treatment against medical advice, eventually resulting in the recurrence of episodes [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high polyunsaturated content and high brain oxygen intake, the central nervous system is susceptible to lipid peroxidation. It also lacks antioxidant enzymes in a significant amount [46][47][48][49]. Plasma MDA levels were found to be higher in people who suffer from depression.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is characterized by a sad mood, pessimistic thoughts, decreased interest in day-to-day activities, poor concentration, insomnia or increased sleep, significant weight loss or gain, decreased energy, persistent feelings of guilt and worthlessness, decreased libido, and suicidal thoughts that last at least two weeks. 1 Patients with depression can be of any gender, age, or background. Fear of stigmatization associated with mental disorders discourages patients from seeking early medical treatment.…”
Section: Introductionmentioning
confidence: 99%